Visual tracking speed threshold in NCAA Division I women`s soccer predicting match performance - Phillips, J.; Andre, T. (Scientific Journal of Sport and Performance, 2023)
Correlations between sport performance and visual training have been previously demonstrated. However, it remains unclear if these relationships exist between visual tracking thresholds and in-competition decision-making metrics. Therefore, the purpose of this study was to investigate the relationship between visual tracking speed (VTS) and soccer-specific performance measures. 19 NCAA Division I soccer players VTS was measured from 1-core session on a 3-demensional multiple object tracking (3D-MOT) software NeuroTracker (NT) and soccer performance metrics were obtained from WyScout. Spearman`s rank order correlation coefficient was utilized to examine potential correlations between criterion variables. There was nonsignificant correlation between VTS score and passing accuracy (r = -0.380). However, there was a strong correlation found between consistency score and passing accuracy (r = 0.650). When examining players based on their positional role, for attacking players there were nonsignificant strong correlation with consistency and passing accuracy (r = 0.730). For defenders, consistency and defensive win rate had a strong correlation (r = 0.731). Although there was no significant correlation seen between VTS and decision-making variables when examining the entire team, there was a significant strong positive relationship between consistency scores and passing accuracy. Future research should seek to include multiple teams for improved sample size.